The Hulks and the Deadpools of the Cytokinin Universe: A Dual Strategy for Cytokinin Production, Translocation, and Signal Transduction - Tomáš Hluska; Lucia Hlusková; R. J. Neil Emery (Biomolecules, 2021)
Cytokinins are plant hormones, derivatives of adenine with a side chain at the N6-position. They are involved in many physiological processes. While the metabolism of trans-zeatin and isopentenyladenine, which are considered to be highly active cytokinins, has been extensively studied, there are others with less obvious functions, such as cis-zeatin, dihydrozeatin, and aromatic cytokinins, which have been comparatively neglected. To help explain this duality, we present a novel hypothesis metaphorically comparing various cytokinin forms, enzymes of CK metabolism, and their signalling and transporter functions to the comics superheroes Hulk and Deadpool. Hulk is a powerful but short-lived creation, whilst Deadpool presents a more subtle and enduring force. With this dual framework in mind, this review compares different cytokinin metabolites, and their biosynthesis, translocation, and sensing to illustrate the different mechanisms behind the two CK strategies. This is put together and applied to a plant developmental scale and, beyond plants, to interactions with organisms of other kingdoms, to highlight where future study can benefit the understanding of plant fitness and productivity.